Toward Integrated Disaster Risk Management in Vietnam : Recommendations Based on the Drought and Saltwater Intrusion Crisis and the Case for Investing in Longer-Term Resilience - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2017)
Vietnam is one of the most hazard-prone countries in the East Asia and Pacific region, with droughts, severe storms, and flooding causing substantial economic and human losses. Climate change is projected to increase the impact of disasters, especially the timing, frequency, severity, and intensity of hydro-meteorological events. Vietnam’s 2015–2016 drought and associated saltwater intrusion (SWI) offer a preview of what could become the new normal, and make clear the need to take action to ensure the country’s economic and societal well-being. SWI developed into a national crisis, with close to two million people affected due to damaged livelihoods and the country seeking international help. This report takes a deeper look at the drought and SWI crisis faced by Vietnam, identifies the gaps across key sectors, and recommends the principal short and longer-term actions needed for integrated disaster risk management. The recommendations are based on global experiences in good governance with intersectoral coordination in disaster forecast and early warning, and in community empowerment in water resource management and agricultural production.